Don't sweat the small stuff and it's all small stuff : simple ways to keep the little things from taking over your life - Carlson, Richard (UK : Yellow Rite, 2017)
Richard Carlson PhD is a stress consultant in private practice, and is the bestselling author of You Can Feel Good Again. With this book, Carlson suggests ways to make life less stressful.
Keywords: Self-actualization (Psychology).; Stress management; Self-management (Psychology)